2024
DOI: 10.3390/agronomy14030406
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Vital Role of ABA Plays in Drought Tolerance of the ABA-Insensitive Alfalfa (Medicago sativa L.)

Mingzhi Xu,
Zhenpeng Xu,
Yanrong Liu
et al.

Abstract: Drought stress severely affects alfalfa (Medicago sativa L.) growth and production. It is particularly important to analyze the key networks of drought in alfalfa through physiological and molecular levels. However, how to quickly screen drought-tolerant alfalfa germplasm and how to elucidate the molecular pathways of alfalfa responding to drought are less studied. In this study, based on our previous research, we further verified the association between the heritability of ABA sensitivity during seed germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Research has shown that the ABA content in alfalfa varies between roots and leaves under drought conditions and is influenced by the duration of the stress ( Ren and He, 2010 ; Gamal et al., 2016 ). The plants that were not sensitive to ABA during germination showed stronger drought tolerance ( Xu et al., 2024 ). Additionally, the accumulation of ABA in alfalfa under drought stress is related to the dynamics of storage proteins, gene expression, and the accumulation of certain osmoregulatory substances in the primary roots ( Li et al., 2015 ).Overall, these physiological and biochemical responses collectively enhance alfalfa’s ability to withstand drought conditions, highlighting the complexity and adaptability of this crop in response to water stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the ABA content in alfalfa varies between roots and leaves under drought conditions and is influenced by the duration of the stress ( Ren and He, 2010 ; Gamal et al., 2016 ). The plants that were not sensitive to ABA during germination showed stronger drought tolerance ( Xu et al., 2024 ). Additionally, the accumulation of ABA in alfalfa under drought stress is related to the dynamics of storage proteins, gene expression, and the accumulation of certain osmoregulatory substances in the primary roots ( Li et al., 2015 ).Overall, these physiological and biochemical responses collectively enhance alfalfa’s ability to withstand drought conditions, highlighting the complexity and adaptability of this crop in response to water stress.…”
Section: Discussionmentioning
confidence: 99%
“…further demonstrated that the miR156/SPL13 module alleviates drought stress in alfalfa through tissue-dependent regulatory molecules and physiological processes ( Fang et al., 2023 ). Moreover, the sensitivity of alfalfa seeds to ABA is heritable, and screening for ABA during seed germination can help select alfalfa lines with better drought tolerance ( Xu et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%